Important training principles for sprinting - Bennett, S.
Pelvic Core stability is an area of strong focus from the start of any athletes career. The better their stability and posture the less problems they may have, the more effective they will be and the harder they can train. Stronger Abs & Back by Brittenham & Brittenham has a great range of exercises and explians trunk training brilliantly. The program recommends a large variety of trunk exercises performed perfectly. Athletes should aim in their programs for a good mix of core stability exercises possibly with a swiss ball and to progress from Ab/back conditioning exercises to strength exercises (as their condition improves) and then possibly for some athletes to Ab/back power exercises. The days of considering 3 sets of 50 situps as good ab work are gone. I consider this a key area in helping an athlete to prevent trunk related injuries eg Hamstring tears. a stable trunk should also provide better balance and relaxation at high speeds.